2014
DOI: 10.1038/jcbfm.2014.143
|View full text |Cite
|
Sign up to set email alerts
|

Reestablishing Brain Networks in Patients without Overt Hepatic Encephalopathy after Liver Transplantation

Abstract: Cirrhotic patients without overt hepatic encephalopathy (HE) have associated with widespread neuro-psychological impairment. Liver transplantation can restore metabolic abnormalities but the mechanisms are unclear. We investigate brain functional networks after transplantation using resting-state funtional magnetic resonance imaging (MRI). Twenty-six cirrhotic patients without overt HE completed neuro-psychological assessment before and 6 to 12 months after transplantation, and compared with 35 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…On the one hand, post‐LT improvement has been shown in the setting of HE on the basis of EEG and PET scan results . On the other hand, MRI studies that use standard sequences, magnetic resonance spectroscopy (MRS), diffusion tensor imaging (DTI), and functional MRI (Table ) can show both improvement in cerebral abnormalities that were present prior to LT because of HE (see Table for review) and persistent abnormalities after LT . Spontaneous T 1 ‐weighted sequence basal ganglia hypersignals, white matter changes in the corticospinal tract, magnetization transfer ratio (MTR), and the HE profile on MRS normalize months after LT .…”
Section: Neurocognitive Complications After Ltmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, post‐LT improvement has been shown in the setting of HE on the basis of EEG and PET scan results . On the other hand, MRI studies that use standard sequences, magnetic resonance spectroscopy (MRS), diffusion tensor imaging (DTI), and functional MRI (Table ) can show both improvement in cerebral abnormalities that were present prior to LT because of HE (see Table for review) and persistent abnormalities after LT . Spontaneous T 1 ‐weighted sequence basal ganglia hypersignals, white matter changes in the corticospinal tract, magnetization transfer ratio (MTR), and the HE profile on MRS normalize months after LT .…”
Section: Neurocognitive Complications After Ltmentioning
confidence: 99%
“…Despite limited data from DTI, it appears that mean diffusivity (MD) decreases after LT, suggesting a correction of vasogenic edema with the normalization of liver function . Only scarce data are available from functional MRI, though what is available also suggests an improvement in the functioning of the previously altered networks after LT . However, several data also suggest persistent cerebral abnormalities after LT. Standard MRI sequences can provide evidence of reduced brain volume and a decrease in the MRS N ‐acetylaspartate (NAA)/creatine (Cr) ratio, both of which suggest the presence of fixed brain lesions and brain atrophy .…”
Section: Neurocognitive Complications After Ltmentioning
confidence: 99%
“…These studies indicated that the impairments and reorganization of brain function are dynamic processes and that these changes can both exist in every stage of HE from simple cirrhosis (without HE) to MHE and, ultimately, overt HE. Using resting-state functional connectivity, Lin et al ( 16 ) found dynamic disruptions and reconstruction of intrinsic large-scale networks approximately one year after LT accompanied by cognitive deficits and recovery. Moreover, Zhang et al ( 17 ) found improved long- and short-range functional connectivity density one month after LT and persistence of posterior cingulate cortex/precuneus (PCu) functional connectivity disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…A compensatory increase in cerebellar flow under hypoxia indicates preferential perfusion of brain regions vital to respiratory and cardiovascular stability [ 49 ]. Adequate treatment for cirrhotic patients may reverse brain edema and re-establish impaired functional connectivity with improvement in cognitive function [ 21 , 50 ]. Investigations between neuronal activity and irreversible adverse outcome in patients with HE are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to pre-processing, the first 10 volumes were discarded to reach a steady-state magnetization and allow the participants to adapt to the scanning noise [ 11 , 15 , 21 ]. Resting-state fMRI data pre-processing was then performed using the Statistical Parametric Mapping (SPM8, Wellcome Department of Cognitive Neurology, London, UK; http://www.fil.ion.ucl.ac.uk/spm/ ) and Data Processing Assistant for rs-fMRI (DPARSF) tools [ 22 ].…”
Section: Methodsmentioning
confidence: 99%